(untitled) (The Research of Medical Science Review, 2025)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is turning out to be an international community wellbeing crisis, whose tableau is interwoven with the expanding speed of metabolic syndrome. Affecting developed as well as developing countries; NAFLD is a silent but gradual disease of the liver that may cause non-alcoholic steatohepatitis (NASH), fibrosis, and cirrhosis and hepatocellular carcinoma. In South Asia including Pakistan, the situation is quite frightening as sedentary lifestyles, unhealthy eating and rising cases of obesity and diabetes are enhancing this epidemic. The disease has an enormous burden, but liver biopsy, considered the gold standard to diagnose a disease, is invasive, costly and inaccessible to most settings. This research considers comparing the diagnostic performance of three non-invasive methods, including Fibro Scan, NAFLD Fibrosis Score (NFS) and FIB-4, in determining liver fibrosis in NAFLD with metabolic syndrome. Methods: The cross-sectional piloting, which was comparative validation, took place among 180 NAFLD patients with metabolic syndrome that was recruited different hospitals across Pakistan. Routine biochemical markers were used to compute FIB-4 and NFS, whereas Fibro Scan measured liver stiffness in a non-invasive manner. Sensitivity, specificity, PPV, NPV and AUC were used to measure statistical values, logistic regression and ANCOVA were applied to determine significant predictors. Results: The results were more pronounced in the diagnosis with Fibro Scan (AUC = 0.998, Sensitivity = 97.9%, Specificity = 96.3%) that was followed by NFS (AUC = 0.985) and FIB-4 (AUC = 0.976). Analysis by regression indicated that NFS was the best independent predictor of fibrosis whereas gender and age exerted a weak effect on liver stiffness measure. Conclusion: Fibro Scan is still the best non-invasive test in detecting liver fibrosis in NAFLD. NFS and FIB-4 have very reliable and economical alternatives, especially in a low resource setting. Introducing the tools in everyday screening methods has the potential to revolutionise NAFLD onset and early treatment in metabolically-syndromic-high-risk groups.